(untitled) (Journal of Universal Science Research, 2023)
This article deals with the importance and opportunities of the Internet in a language learning process.It is given that the utilization of the Internet,including networking sites,online platforms for communicating with foreigners provides learners with a good source of manual materials,video lessons and good language learning environment.The benefits and aspects of the information-communicative technologies in educational system is indetail shown.There is no doubt that learning a language with using such kind of technologies is hopefully best way.